The Impact of Peer-Helper Program on Peer Helpers: Some Preliminary Findings - TAN, Yip Wei, Gilbert (Institutional Knowledge at Singapore Management University, 2007)
The Singapore Management University (SMU) initiated a peer helping program in January 2004 for the purpose of having the helpers act as a “bridge” between the University counseling service and the student community. Over the years, the peer helping program has broadened to include wellness education in addition to providing peer counseling, mentoring and mediation services for the student community. Although most of the students who volunteered for the program have demonstrated strong intrinsic desires to assist and to help others, the writers of this paper are of the opinion that the benefits of peer helping extends to both the client and the helper as well. This paper reports our findings on the impact of the peer helping program on our peer helpers. A questionnaire designed to measure the perceived benefits of being involved the peer helping program was administered to all the peer helpers. We use the retrospective pretest method to track changes in the measures (Nimon & Allen, 2006). Our study shows that the peer helpers have grown and developed as the result of their involvement in the peer helping program. Specifically, our peer helpers reported improvement in (a) self-awareness, (b) emotional awareness of others, and, (c) organization-based self-esteem (OBSE). In addition, peer helpers benefited from learning specific counseling skills like reflecting feelings and asking probing questions and acquiring practical life skills like inter-personal effectiveness and emotion management. The success of the peer helper program at SMU can be gauged by the overwhelming support by the peer helpers. 93.3% of them indicate that they would recommend the program to their friends.